Perbandingan Pemilihan Moda Transportasi Online dan Transportasi Konvensional pada Keseharian Siswa Madrasah Aliyah Negeri Kota Sorong - Rahayu Erwi Yani Putri; Musvira Febriana Umar; Andi Rahmat (CV. Shofanah Media Berkah, 2025)
This study aims to analyze the factors influencing students’ decisions in choosing transportation modes to school at Madrasah Aliyah Negeri (MAN) Kota Sorong, focusing on a comparison between online transportation and conventional transportation. The variables examined include cost, travel time, safety, and comfort. The research employed a descriptive quantitative approach using binary logistic regression analysis. Data were collected through questionnaires distributed to 100 respondents who were active students of MAN Kota Sorong. The results indicate that cost, travel time, and safety have a significant effect on transportation mode choice, while comfort does not have a significant influence. The regression coefficient for the cost variable is −0.818 (Sig. < 0.001), indicating a negative relationship with the selection of online transportation, meaning that higher perceived costs reduce the likelihood of students choosing online transportation. Meanwhile, travel time has a coefficient of 0.698 (Sig. 0.003) and safety has a coefficient of 0.280 (Sig. 0.049), both of which show a positive and significant effect on the choice of online transportation. The highest odds ratio is found in the travel time variable (Exp(B) = 2.009), indicating that improved travel time efficiency increases the probability of students choosing online transportation by approximately two times compared to conventional transportation. Overall, the findings suggest that cost and travel time are the dominant factors in students’ transportation mode choice at MAN Kota Sorong. Students who are sensitive to transportation costs tend to choose conventional transportation due to its lower fares, while those who prioritize time efficiency and safety are more likely to select online transportation.